Microstructural properties of white matter pathways in relation to subsequent reading abilities in children: A longitudinal analysis - Borchers, Lauren R. (Brain Struct Funct, 2018)
Microstructural properties of white matter pathways are associated with concurrent reading abilities in children. In this longitudinal study, we asked whether properties of white matter pathways at the onset of learning to read would be associated with reading abilities at older ages. Children (N=37) with a wide range of reading abilities completed standardized measures of language and phonological awareness and diffusion MRI at age 6 years. Mean tract-fractional anisotropy (FA) was extracted from reading-related pathways. At age 8, the same children were reassessed using a standardized reading measure. Using linear regressions, we examined the contribution of tract-FA at age 6 to reading outcome at age 8, beyond known demographic and pre-literacy predictors of reading. Tract-FA of the left arcuate, left and right superior longitudinal fasciculus (SLF), and left inferior cerebellar peduncle (ICP) made unique contributions to reading outcome after consideration of sex and family history of reading delays. Tract-FA of the left and right SLF and left ICP made unique contributions to reading outcome after the addition of preliteracy skills. Thus, cerebellar and bilateral cortical pathways represented a network associated with subsequent reading abilities. Early white matter properties may be associated with other neuropsychological functions that predict reading or may influence reading development, independent of reading-related abilities. Tract-FA at early stages of learning to read may serve as a biomarker of later reading abilities.